1998
DOI: 10.1177/002215549804600602
|View full text |Cite
|
Sign up to set email alerts
|

Rat Endocrine Pancreatic Development in Relation to Two Homeobox Gene Products (Pdx-1 and Nkx 6.1)

Abstract: SUMMARYWe studied the distribution of the homeodomain proteins Pdx-1 and Nkx 6.1 in the developing rat pancreas. During early development, nuclear staining for both Pdx-1 and Nkx 6.1 occurred in most epithelial cells of the pancreatic anlage. Subsequently, Nkx 6.1 became more ␤ -cell-restricted, and Pdx-1 also occurred in other islet cell types and in the duodenal epithelium. During early pancreatic development, cells co-storing insulin and glucagon were regularly detected. The vast majority of these did not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 41 publications
10
83
0
2
Order By: Relevance
“…It is generally believed that the endocrine, exocrine and ductal cell types are derived from endodermal cells [5]. Several studies have shown that the endocrine stem cell require several specific transcription factors to mature into single-hormone-expressing cells [6,7,8,9]. The pancreatic duodenum homeobox 1 (PDX-1) has been shown to be important both for pancreas development [26] and subsequent maturation of the endocrine cells [27], whereas later in the mature islets PDX-1 expression is restricted to the insulin-producing beta cells [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is generally believed that the endocrine, exocrine and ductal cell types are derived from endodermal cells [5]. Several studies have shown that the endocrine stem cell require several specific transcription factors to mature into single-hormone-expressing cells [6,7,8,9]. The pancreatic duodenum homeobox 1 (PDX-1) has been shown to be important both for pancreas development [26] and subsequent maturation of the endocrine cells [27], whereas later in the mature islets PDX-1 expression is restricted to the insulin-producing beta cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the endocrine stem cell require several specific transcription factors to mature into single-hormone-expressing cells [6,7,8,9]. The pancreatic duodenum homeobox 1 (PDX-1) has been shown to be important both for pancreas development [26] and subsequent maturation of the endocrine cells [27], whereas later in the mature islets PDX-1 expression is restricted to the insulin-producing beta cells [8]. Another transcription factor, Nkx-6.1, is important for maturation of the insulin-producing beta cells [8], whereas Brain-4 is important for maturation of the glucagon-producing α-cells [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…c-fos, c-jun, junD and nur77 [28,29]. GLP-1 increases the DNA binding activity and expression level of the beta-cell-specific transcription factor pancreatic and duodenal homeobox gene-1 (PDX-1) [30,31], which is implicated in regulating expression of the insulin, GLUT2 and glucokinase genes, and in the regulation of beta cell differentiation [32,33,34]. GLP-1 mobilises intracellular Ca 2+ [35,36] via cyclic AMP guanine nucleotide exchange factor 2 (Epac) [37], an effect that may contribute to the insulinotropic action of the peptide.…”
Section: Introductionmentioning
confidence: 99%